Transportation and recycling management system of UPSB, UUM - Nazir, Azimah; Zainuddin, Nizamuddin (2012)
This study aims to identify the important of transportation and recycling management system that systematic to party UPSB and give interest to all UUM student.Focus of study is on transport interest in carry rubbish all over UUM with method that more systematic and save time.This study operate against all UUM student and also staffed in UUM randomly chosen stratified and a sets of questionnaires used as study instrument to collect data. Data achieved analyzed use descriptive statistics or Statistical Product and Service Solutions (SPSS) to interpret data and to respond study questions. Retrieval research showed that aspect level UUM student tendency and also staffs UUM have medium yarn awareness level on transport interest in carry rubbish all over UUM by party UPSB. As an effort solution, an integrated approach has been chosen to manage the problem for UPSB.